Factors influencing antibiotic prescribing habits and use of sensitivity testing amongst veterinarians in Europe. (16th November 2013) - De Briyne, N.; Atkinson, J.; Pokludová, L.; Borriello, S. P.; Price, S.
Abstract : The Heads of Medicines Agencies and the Federation of Veterinarians of Europe undertook a survey to gain a better insight into the decision‐making process of veterinarians in Europe when deciding which antibiotics to prescribe. The survey was completed by 3004 practitioners from 25 European countries. Analysis was to the level of different types of practitioner (food producing (FP) animals, companion animals, equines) and country for Belgium, Czech Republic, France, Germany, Spain, Sweden and the UK. Responses indicate no single information source is universally considered critical, though training, published literature and experience were the most important. Factors recorded which most strongly influenced prescribing behaviour were sensitivity tests, own experience, the risk for antibiotic resistance developing and ease of administration. Most practitioners usually take into account responsible use warnings. Antibiotic sensitivity testing is usually performed where a treatment failure has occurred. Significant differences were observed in the frequency of sensitivity testing at the level of types of practitioners and country. The responses indicate a need to improve sensitivity tests and services, with the availability of rapid and cheaper testing being key factors.